SIFAT PEMESINAN BEBERAPA JENIS KAYU DARI DAERAH KALIMANTAN BARAT DAN JAWA BARAT - Osly Rachman; Jamal Balfas (Jurnal Penelitian Hasil Hutan, 1989)
Machining  properties   of  16  wood  species  from   West Kalimantan   and  West Java has been  identified   using the  modified  ASTM   D-1666  which  was described  in the  Forest  Products   Research  Institute  Report   No.  160  (1982).   The  samples (25 pieces/species)    were dried  to  equilibrium   moisture   content   condition   (15  to  18% of MC).  The  machining  properties tested  are planing,  shaping,   boring,  turning  and  sanding.Seven  species  that  have  good   to  very  good  machining  properties   are  kenari  I, kenari II,  kemayau,   belangeran,  ki sampang,  ki  endog  and  surian  bawang.   The  best  machining properties,   however,   were  found   on johar,  gadog and putat. Whereas the  other  species  are good  or  very good  in some  properties   and  fair or  even poor  in others,